A quality of service based planning for IEEE802.11g networks. (6th April 2009) - Aouam, Tarik; Boulmalf, Mohammed; Harroud, Hamid
In this article, we propose a network planning algorithm for IEEE802.11g, which minimises the total interferences between access points while maintaining a required quality of service (QoS), measured by users' signal to interference ratio (SIR). Three planning problems are formulated as integer linear programs. (1) A frequency assignment problem, which assigns frequencies to access points while minimising total interferences and ensuring users' SIR higher than a required threshold. (2) Assuming the optimal frequency assignment, a power management problem is modelled to assign five different power levels to access points while reducing the network total interference and ensuring the required QoS is met. (3) Given the frequency and power assignments, a load balancing problem is formulated to minimise the maximum number of users assigned per access point, taking into consideration users' QoS. Once the planning is done, new joining users are dynamically assigned to the less loaded acceptable access point. Based on realistic scenarios analysis, we show that the proposed planning achieves significant improvement in average user SIR and power savings while balancing the network. In fact, for one of the analysed scenarios the algorithm achieved 55% power savings while the SIR increased by 6 dB improving the QoS.